A General Synthesis of Benzoazepinoindoles – A New Class of Heterocycles - Dobrowolski, Jeremy C.; Nguyen, Duyen H.T.; Fraser, Benjamin H.; Bhadbhade, Mohan; Black, David StC.; Kumar, Naresh (Synlett, 2019)
A new class of heterocyclic compounds, namely the benzoazepinoindolones, has been synthesised through a base-catalysed cyclisation reaction of 1,4-bis(2-aminophenyl)-2-phenylbutane-1,4-dione derivatives and features the prominent seven-membered azepine ring moiety. This synthesis has considerable scope for the rapid generation of more complex structures and is inexpensive and generally applicable.
Keywords: dihydrobenzo[6,7]azepino[3,2-c]indolones; fused-ring systems; umpolung; condensation; heterocycles